On the Optimal Composition of Committees - Ruth Ben-Yashar; Leif Danziger (Institute for the Study of Labor (IZA), 2014)
This paper derives a simple characterization of how to optimally divide an organization's experts into different decision-making committees. The focus is on many three-member committees that make decisions by a simple majority rule. We find that the allocation of experts to committees is optimal if and only if it minimizes the sum of the products of the experts' skills in each committee. As a result, given the experts of any two committees, the product of the experts' skills should be as similar as possible in the two committees, and it is never optimal to have the three worst experts in one committee and the three best experts in another.
Keywords: D71; 330; optimal composition of committees; simple majority rule